E-Readiness Model for its Adoption in District Government Institutions - Fajar Surya G, Soni; Nugroho, Heru (International Journal of Engineering and Technology, 2026)
One of the biggest challenge faced by government institution lying on readiness level of information technology (e-Readiness) being adopted. The aims of this study is to produce E-readiness model for assesment of Information Technology adoption in Government Institution. This study used Design Science Research Methodology (DSRM) using 7 enablers of COBIT 5 as variables by participating government institution in Bandung District. The analysis was performed on 7 enterprise enabler namely behaviour, information, application and infrastructure services, skills and competencies of Human Resources, while interviews, observations, and quuestionnaire was conducted during data collection. The results revealed Business Process, Organization Structure, Culture, Ethic and Behaviour, information and skill and competence have significantly affect e-Readiness of IT adoption in government institution of Bandung District.
Keywords: e-Readiness; Government; COBIT 5; IT Adoption